2021
DOI: 10.2217/imt-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Lung Immune Prognostic Index as a Biomarker in Advanced Non-Small-Cell Lung Cancer Patients Receiving First Line Pembrolizumab

Abstract: Background: To investigate the role of pretreatment lung immune prognostic index (LIPI) as biomarker in PD-L1 ≥50% non-small-cell lung cancer patients receiving pembrolizumab. Patients & methods: We retrospectively identified 117 patients, divided into 3 prognostic groups according to LIPI score. For each patient, we evaluated 1-year overall survival (OS) and progression-free survival rate. C-statistic and survival receiver operating characteristic curves were used to study discrimination of LIPI. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Moreover, retrospective database studies can be marred by errors in recording data and failure to collect some information. For example, biological data were missing for nearly half of the patients, explaining why LIPI (Lung Immune Prognostic Index) score was not mentioned in our analysis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, retrospective database studies can be marred by errors in recording data and failure to collect some information. For example, biological data were missing for nearly half of the patients, explaining why LIPI (Lung Immune Prognostic Index) score was not mentioned in our analysis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…LIPI is a comprehensive inflammatory factor composed of dNLR and LDH (24). LIPI was relevant with inflammatory status and has recently been widely reported as a novel prognostic factor in lung cancer and extra-pulmonary cancer ( Mezquita et al, 2018 ; Kazandjian et al, 2019 ; Sonehara et al, 2020 ; Auclin et al, 2021 ; Feng et al, 2021 ; Veccia et al, 2021 ; Xie et al, 2021 ; Obayashi et al, 2022 ). More inspiring, studies have shown that LIPI can not only predict the survival but also excellently predict the response to immunotherapy ( Mezquita et al, 2018 ; Auclin et al, 2021 ; Feng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%